HUBUNGAN ANTARA ADVERSITY QUOTIENT DENGAN INTENSI BERWIRAUSAHA PADA MAHASISWA UNIVERSITAS JAMBI - Muhammad Ilham (Jurnal Psikologi Universitas HKBP Nommensen, 2020)
This study aimed to determine the relationship between adversity quotient with entrepreneural intention in student of Jambi University. This study used a quantitative research method with a correlational research approach. Sampling used Accidental sampling technique. This research was conducted at the University of Jambi. The subjects used in this study were 110 student of Jambi University. This study used the scale of adversity quotient and entrepreneurial intention, and the analytical method used is the Pearson's Product Moment correlation technique. This study shows there is a significant positive relationship between the two variables. The contribution to the value of the correlation coefficient (r) is 0.516 with p equal to 0.001 (p <0.05). The coefficient of determination (R2) in this study, adversity quotient contributed as much as 26.6% to the intention of entrepreneurship, while 73.4% of the others were contributions from other factors that were not the focus of this study.This variable correlation has a positive direction indicating the higher the adversity quotient, the higher the intention of entrepreneurship will be. Student who have been known to have adversity uotient and high entrepreuneral intention, can be directed and facilitated by the university to take part in entrepeuneral programs. Keywords: adversity quotient, entrepreneurial intention